PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID UNTUK MOTIVASI SISWA SMP MUHAMMADIYAH CIANJUR - Nani Kustini; Dirgantara Wicaksono (Taksasila Edukasi Insani, 2025)
This study aims to develop a valid, practical, and effective Android-based social studies learning media using Articulate Storyline to increase the learning motivation of 8th-grade students at SMP Muhammadiyah Cianjur. Conventional learning methods have been observed to be teacher-centered and lack technological integration, causing boredom and low student motivation. This research uses the Research and Development (RD) method with the ASSURE model (Analyze, State, Select, Utilize, Require, Evaluate/Revise). Data were collected through expert validation questionnaires, student response questionnaires, and pre-test/post-test. The results showed that the developed media was declared